PRO-ACTIVE PROPOSAL [ON] HIRING DISCRIMINATION (Tufts Archival Research Center, 2007)
Report outlining a pro-active proposal on hiring discrimination in Missouri in 1990. Proposes introducing a bill to prohibit employment discrimination practices against individuals who smoke. Identifies resources needed to gain proponents of the bill as: legal memorandum, coalition allies, Tobacco Institute grassroots mobilization, company resources and possible media resources.